Factors Associated with Depression Symptoms in the Peruvian Population: Analysis of a National Health Survey - Zeñas-Trujillo, Gianella zulema; Vera-Ponce, Víctor Juan (European Journal of Mental Health, 2024)
Introduction: Worldwide, approximately 280 million people suffer from depression, which results from complex interactions. Aim: Determining the prevalence of depressive symptoms and their associated factors in the Peruvian Population. Methods: Analytical cross-sectional study. The odds ratios together with their 95% confidence intervals were calculated. For evaluating the strength of association between the variables of interest, a generalized linear model of the Poisson family was performed with robust variance. Results: The factors associated with exhibiting symptoms of depression were: the female sex; the age group older than 70 years; the year 2021; being married, cohabiting and being separated; residents in the region of Lima, the rest of the coast, mountains and jungle; possessing a level of higher education; living in a rural area; physical disability; drinking alcoholic beverages; having type 2 diabetes mellitus; having hypertension; medium and high fruit consumption. Conclusions: All the variables evaluated, except for the wealth index, tobacco consumption, health insurance, and body mass index, were associated with depressive symptoms.